Awareness and Utilization of Computers by Shrimp Farmers - P., Mahalakshmi; B., Shanthi; M., Krishnan; Vimala, D.D.; C., Sarada (Fishery Technology, 2025)
A study was conducted in Thiruvallur and Thoothukudi districts of Tamil Nadu to assess the shrimp farmers awareness and utilization of computers, and their constraints. The major sources of awareness utilized by the farmers are personal localite channels like fellow farmers and friends (42 percent) and mass media channels (34 percent) followed by, extension agency contact (18 percent), and internet (8 percent). Regression analyses on the awareness scores among the respondents revealed that the eight independent variables explained 71 percent of the variance in the farmers' awareness on use of computers. Further the results also revealed that four variables viz., age, farming experience, farm size, and mass media exposure would have to be strengthened to increase the awareness on the utility of computers in shrimp farms. 78 percent of the respondents used computers for non-aquacultural activities followed by 4 percent of them who had exposure to programming and database design, and 22 percent of the respondents had exposure to e-mail services. Lack of technical knowledge and technical support were the main constraints found in the awareness and utilization of computers by shrimp farmers.